P067 Fractal analysis of extracellular matrix as a new histological method for observer-independent quantification of intestinal fibrosis in Crohn's Disease. (30th January 2023) - Weber, M C; Schmidt, K; Buck, A; Kasajima, A; Becker, S; Wilhelm, D; Friess, H; Neumann, P A
Abstract: Background: The prevention of intestinal fibrosis formation is still an unsolved problem in the management of Crohn's Disease (CD) as no specific antifibrotic therapies are available yet. Appropriate analysis of fibrosis severity is essential to assess the therapeutic efficacy of potential anti-fibrotic drugs. However, up to now, no standardized method exists, that allows for automated observer-independent histological evaluation of intestinal fibrosis severity. The aim of this study was thus to develop an objective and observer-independent histological method for the quantification of intestinal fibrosis in surgical specimens of Crohn's patients using structural analysis of the extracellular matrix (ECM). Methods: To quantify the structural complexity of the total ECM, fractal dimension analysis was performed using the FracLac plugin in FIJI/ImageJ in fibrotic and control sections of surgical specimens from patients with CD (n = 28) stained with Masson's trichrome. To selectively assess the structure of the collagen matrix, polarized light microscopy was used on Picrosirius red-stained sections. A score to quantify collagen fiber alignment and the color of the polarized light was established. As a reference, sections were scored by a pathologist using an established histological fibrosis score (0 - 4), the proportionate collagen fraction was measured and COL1A1 and COL3A1 mRNA expression was assessed. Results: Fractal dimension as a measure for the structural complexity correlated significantly with the histological fibrosis score (r = .68, p < .0001), and differences in fractal dimension differed significantly between sections with different fibrosis scores, indicating that during fibrosis progression, there is not only an accumulation of ECM but also structural changes within the ECM network. Using Picrosirius polarized light microscopy, we found that sections with low fibrosis scores showed a meshwork-like alignment of the collagen fibers while sections with high fibrosis scores showed a parallelization of long collagen fibers. Fiber alignment (r =.71, p < .0001) positively correlated with the histological fibrosis score. All measurements were significantly higher in sections from the fibrotic focus compared to the resection margin. Conclusion: Fractal dimension analysis was suitable for fibrosis quantification in histological samples from surgical specimen of CD patients. Picrosirius polarized light microscopy underlined our findings on structural changes of the ECM network during fibrosis progression in CD. Automated structural analysis of the ECM network using fractal analysis has the potential to serve as an observer-independent histological tool for fibrosis quantification in surgical specimens of patients with CD.